Navigating Do-Not-Resuscitate Orders in the Emergency Department: a Case Report on Ethical Decision Making - Hersinta Retno Martani; Rizki Puji Agustin; Ninuk Dian Kurniawati; Suis Galischa Wati; Sriyono (Talenta Publisher, 2025)
A patient with Chronic Kidney Disease Stage V presented to the Emergency Department (ED) with severe shortness of breath, caused by pulmonary edema resulting from non-compliance with fluid restriction. The patient and her husband consented to the use of a mechanical ventilator and dialysis; however, they declined to authorise cardiac and pulmonary resuscitation in the event of cardiac arrest or to establish a Do-Not-Resuscitate (DNR) order. This presents a dilemma, as patients with requiring ventilatory support typically necessitate ICU admission; nevertheless, patients with DNR orders are generally not admitted to ICU. The situation worsened when the extended family opposed the DNR Order established by the patient and her husband. This case report aimed to provide solutions for nurses addressing ethical dilemmas concerning the determination of DNR orders. This case report follows the CARE Case Report Guidelines. Following immediate and continuous care in the emergency department and intensive care unit, the patient demonstrated significant improvement. The nurse resolved ethical issues by organizing a family conference that included the patient’s family and care team, discussing the treatment plan on the basis of the most recent assessment results. Nurses’ proactive engagement of multiple stakeholders in patient care within the hospital effectively addresses Do-Not-Resuscitate order-associated ethical dilemmas. To effectively address ethical conflicts, nurses should improve their emphatic communication skills, prioritizing patient interests. Keyword: Do-Not-Resuscitate, Ethical dilemmas, Decision making, Advance care planning, Case report